FOOD CONSUMPTION AND BEHAVIOR OF UNIVERSITY EMPLOYEES: A CROSS-SECTIONAL STUDY - Antônio Augusto Schäfer; Antonio José Grande; Micaela Rabelo Quadra; Fernanda Oliveira Meller (Universidade do Estado do Rio de Janeiro, 2019)
Objective: To evaluate the consumption and eating habits of university employees. Methods: A cross-sectional study was carried out with a representative sample of workers at the University of Criciúma-SC. The frequency of consumption of vegetables, fruits, meats, soda, artificial juice and sweets was evaluated, according to the following response options: "never", "almost never", "1 to 2 days", "3 to 4 days", "5 to 6 days" or "daily". Regular consumption was defined by consumption of five days or more. Number and location of meals, eating in front of the television, consumption of meat fat and addition of more salt to food was also assessed. Analyzes were performed using Stata version 12.1. Results: 214 employees were studied. A half of them consumed regularly fruits and vegetables. About 20% of the workers referred regular consumption of sweets, soda and artificial juice. Also, approximately 50% of the sample studied had at least five meals a day and had the habit of eating while watching television. Conclusion: Employees showed low frequency of consumption of foods considered markers of healthy eating, such as fruits, vegetables and beans. Moreover, many of them reported having inappropriate eating behavior. Thus, it is necessary to implement nutrition promotion and prevention actions at the University focused on nutrition. DOI: 10.12957/demetra.2019.38102